A note on Systena frontalis [Coleoptera : Chrysomelidae] adults on lowbush blueberry, Vaccinium angustifolium - Maltais, P.M.; Ouellette, M.C.. (Phytoprotection, 2000)
Systena frontalis, the red-headed flea beetle, is reported for the first time feeding on the foliage of lowbush blueberry, Vaccinium angustifolium.